N‐Linked Glycans in the Variable Domain of IgG Anti–Citrullinated Protein Antibodies Predict the Development of Rheumatoid Arthritis. Issue 10 (2nd September 2019) - Hafkenscheid, Lise; de Moel, Emma; Smolik, Irene; Tanner, Stacey; Meng, Xiaobo; Jansen, Bas C.; Bondt, Albert; Wuhrer, Manfred; Huizinga, Tom W. J.; Toes, Rene E. M.; El‐Gabalawy, Hani; Scherer, Hans U.
Abstract : Objective: Anti–citrullinated protein antibodies (ACPAs) are disease‐specific biomarkers in rheumatoid arthritis (RA). More than 90% of IgG ACPAs harbor N ‐linked glycans in the antibody variable (V) domain. The corresponding N ‐glycosylation sites in ACPA V‐region sequences result from somatic hypermutation, a T cell–dependent process. As ample evidence indicates that T cells drive the maturation of the ACPA response prior to arthritis onset, we undertook this study to investigate whether the presence of glycans in IgG ACPA V domains predicts the transition from predisease autoimmunity to overt RA. Methods: We analyzed 2 independent sets of serum samples obtained from 126 ACPA‐positive first‐degree relatives (FDRs) of RA patients. Both sets originated from an Indigenous North American population and comprised cross‐sectional and longitudinal samples of individuals who did or did not develop inflammatory arthritis. Serum IgG ACPAs were affinity‐purified and subjected to ultra high‐performance liquid chromatography–based glycan analysis. Results: In both data sets, FDR‐derived IgG ACPA displayed markedly lower levels of V domain glycans (<50%) compared to IgG ACPA from RA patients. Notably, FDRs who later developed RA showed extensive V‐domain glycosylation before the onset of arthritis. Moreover, IgG ACPA V‐domain glycosylation was strongly associated with future development of RA (hazard ratio 6.07 [95% confidence interval 1.46–25.2]; P = 0.013). Conclusion: Extensive glycosylation of the IgG ACPA V domain is present in a subset of predisposed FDRs of Indigenous North American RA patients. The presence of this feature substantially increases the risk of RA development. Based on these findings, we propose that glycosylation of the IgG ACPA V domain represents a predictive marker for RA development in ACPA‐positive individuals and may serve to better target prevention measures.